Determinants of MSME Income in Jambi City - Erwati, Misni; Lutfi, Lutfi; Kusumastuti, Ratih; Afriantoni, Afriantoni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Income is something matter important point in achieved purpose and sustainability business carried out. This study aim for test aspects influential determinants to MSME income in Jambi City, testing influence of business capital, costs power work, and technology information to Jambi City MSME income. Study This using the primary data obtained through questionnaire to Jambi City MSMEs and the samples used in the research This is 150 respondents with technique taking sample use random sampling method. Analysis techniques in study This are there descriptive statistics and analysis regression multiples using SPSS version 25 software, results study prove that : Business capital, costs power work, and technology information influential to Jambi City MSME income, business capital influential to MSME income. That thing show that the more The higher the business capital owned by MSMEs, the more well as support For get income, Costs power Work influential to city MSME income jambi. That thing show that the more tall cost power work issued by MSMEs should be will support For produce high income, Technology information influential towards Jambi City MSME income. That thing show that the more tall technology information used by MSMEs, then will can support For get high income.